Passively Q-Switched Erbium-Doped Fiber Laser via Evanescent Field Interaction with Few-Layer Molybdenum Ditelluride - Man Wu; Ying Li (Advances in Condensed Matter Physics)
We demonstrate an all-fiberized passively Q-switched erbium-doped fiber laser (EDFL) via evanescent field interaction between molybdenum ditelluride saturable absorber (SA) and guided mode of the D-shaped fiber. By integrating the few-layer molybdenum ditelluride prepared by CVD method onto the side-polished fiber, the SA can be realized by the strong interaction between the evanescent field of the waveguide and the nonlinear optical material. The proposed passively Q-switched EDFL could deliver output pulses at 1566 nm wavelength with pulse width of 5.03 μs, a repetition rate of 13.9 kHz, a pulse energy of 150.6 nJ, and an output power of 2.1 mW when pumped by a 980 nm laser diode of 180 mW.